1968
DOI: 10.1111/j.1469-185x.1968.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Motility in Procaryotic Organisms: Problems, Points of View, and Perspectives

Abstract: Summary 1. Procaryotic motility mechanisms are more difficult to investigate than those of the generally larger, hence more easily observable, eucaryotic forms. Furthermore, although the function—namely translational locomotion—is the same, the biomechanisms by which this end is accomplished may be, in fact, quite distinct in the two forms. 2. Observational techniques for studying procaryotic motility are relatively crude and qualitative. Progress toward a greater understanding of motility phenomena will be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

1969
1969
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(40 citation statements)
references
References 189 publications
2
38
0
Order By: Relevance
“…A gap, synapse, or an equivalent thereof, and a primitive 'muscle-membrane' or contractile element, may be coupled with, and activate, a rigid or semirigid non-contractile flagellum. The chemical events may be similar to those found in higher animals, based upon acetylcholine (Doetsch & Hageage, 1968).…”
Section: J L Smith a N D R N Doetschsupporting
confidence: 76%
See 3 more Smart Citations
“…A gap, synapse, or an equivalent thereof, and a primitive 'muscle-membrane' or contractile element, may be coupled with, and activate, a rigid or semirigid non-contractile flagellum. The chemical events may be similar to those found in higher animals, based upon acetylcholine (Doetsch & Hageage, 1968).…”
Section: J L Smith a N D R N Doetschsupporting
confidence: 76%
“…A theory developed by us, in the course of laboratory experiences with various flagellated bacteria (Doetsch, 1966 b; Doetsch, Cook & Vaituzis, 1967) suggested that the flagellum or flagellar fascicle is part of an excito-motor system developed for spacial accommodation. Stimuli are considered to be ' sensed ' by the cytoplasmic membrane acting as a 'monitor' or signal receptor.…”
Section: J L Smith a N D R N Doetschmentioning
confidence: 99%
See 2 more Smart Citations
“…Gliding involves the slow smooth movement of cells in the direction of their long axis without the use of flagella (2,12,14). Although models for gliding motility have been proposed (3,4,6,23,24,28,31), the mechanism of gliding is not understood, and the components of the motility apparatus have not been identified. Highly ordered strands have been observed by electron microscopy in Myxococcusfulvus (24).…”
mentioning
confidence: 99%